PERUBAHAN STRUKTUR EKONOMI DAN PENENTUAN SEKTOR UNGGUL KOTA BALIKPAPAN: ANALISIS INPUT-OUTPUT DAN MFEP - , SITI PATIMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Balikpapanâs average economy growth constantly above East Kalimantan Province (2000â2008), but there were still problems, namely unemployment rate with an rise trend, poverty, inflation, and GDP with a large contribution from sector which based on non-renewable resource (petroleum refinery industry). The purpose of this study are to analyze sectoral role at Balikpapan economy structure in 2000 - 2008, economic structure changes, the impact of extraction Petroleum Refinery Industry Sector and determine priority sector of Balikpapan as efforts to achieve sustainable economic development in Balikpapan. Research conducted with Input-Output Analysis and MFEP. Data processing was done by PyIO software. Sector role in Balikpapan economy indicated that petroleum refinery industry sector was a sector that played the biggest role in gross value added, output, final demand, the highest forward linkage and the highest export index multiplier. Domestic production increased from 2000 to 2008 (11.47 percent), but still high dependence on imports. Structure of final demand indicated that although exports were the highest composition (73.73 percent in 2008) but export earnings became ineffective because of high imports (56.13 percent). Key sectors of Balikpapan were dominated by industrial sector (manufacturing). Industry sectors dominance were seen also from the high share of output, value added, output multiplier and exports index multiplier. This indicated that Kaldor's Growth Law applicable in Balikpapan economy. Economic structure of Balikpapan changed based on economic landscape visualization in 2000 and 2008. Economic landscape shift showed the highest total MPM trade sector in 2000 dropped to sixth in 2008. Total MPM of transport sector up to first place in 2008. Economic structure of Balikpapan still have relevance to economic base 2000, especially related to the dominance of petroleum refining industry sector, despite increase in the role of other sectors (transport, non-metallic products industry, banks, service companies and electricity). Indicators of economic structure changes showed the growing role of secondary and tertiary sectors were followed by decline primary sector role in the formation of output, value added, demand, employment and key sectors. The impact of extraction of petroleum refinery industry sector through HEM analysis indicates that this sector is a strategic sector that was seen from extraction impact of total output loss reached 51.63 percent or Rp20,16 Trillion. Based on MFEP analysis priority sectors that can be developed to realize sustainable economic development in Balikpapan comes from service and industrial sectors with importance role of infrastructure.